Advances in Obesity Treatment: Current Approaches and Future Perspectives - Lachór, Wojciech Wiesław; Solarz, Monika Barbara; Piekarska, Julia; Solarz, Justyna Maria; Wawrzyńców, Jakub Tomasz; Cyrkler, Weronika; Robak, Jakub; Telega, Stanisław; Bollin, Paweł; Szymczak, Urszula (Quality in Sport, 2025)
Obesity is a chronic metabolic disease with a complex etiology, the effective treatment of which requires an interdisciplinary and personalized approach. The aim of this review is to present current and emerging therapeutic strategies used in the treatment of obesity, taking into account their efficacy, safety, mechanisms of action, and potential for clinical application. This analysis includes 20 scientific publications from the years 2020–2024, covering conventional interventions such as lifestyle modification, pharmacotherapy, and bariatric surgery, as well as innovative approaches including transdermal drug delivery systems (TDDS), microbiota-based therapies, immunonutrition, acupuncture, and biomarker-guided treatment. The findings of this review highlight the increasing effectiveness of modern incretin-based medications and the importance of combination therapies. The need for further research on the role of gut microbiota and new technologies in therapeutic outcomes is emphasized. Key challenges in personalizing obesity treatment were identified, along with the significance of psychosocial factors. Effective obesity therapy requires the integration of various treatment strategies tailored to the individual patient’s profile.